Successful Desensitization of a Patient with Aplastic Anemia to Antithymocyte Globulin - Stephanie A. Wolanin M.D.; Jeffrey G. Demain M.D.; Eric A. Meier M.D. (Allergy & Rhinology, 2015)
Antithymocyte globulin (ATG) is a polyclonal gamma immunoglobulin derived from either rabbit or equine serum that serves as therapy for aplastic anemia; however, ATG causes serum sickness in up to 70% and anaphylaxis in up to 5% of recipients. Intradermal (ID) skin testing has been the primary technique used to evaluate for a preexisting Gell and Coombs type I hypersensitivity reaction to ATG. There are no data reporting the predictive value of delayed reactions to ID testing on the risk of serum sickness. This study was designed to establish the importance of epicutaneous and ID skin testing before the administration of ATG through a case report and literature discussion. We report a patient with severe aplastic anemia that was successfully desensitized to ATG after a negative epicutaneous skin test and positive ID skin test. The patient had neither systemic nor localized reactions during the desensitization. Desensitization to ATG in patients with positive epicutaneous skin testing has been shown to be associated with serious and potentially life-threatening complications and should only be considered when the benefits outweigh the risks. Epicutaneous skin testing should be considered in conjunction with ID skin testing when screening for potential sensitivity to ATG. Because of the serious risk of anaphylaxis, desensitization should be performed in an intensive care unit setting in conjunction with a physician familiar with drug desensitization and the management of anaphylaxis.